Performance indicators of state institutions as national innovation system parameters - D. A. Serpukhovitin (E-Management, 2023)
Based on the analysis of the domestic and foreign authors’ papers, a list of 21 parameters characterizing national innovation system state of the Russian Federation has been synthesized. The classification of parameters has showed the possibility of dividing national innovation system of the Russian Federation into two subsystems, the effectiveness of which constitutes its total performance. Two sets of driver parameters have been highlighted and relevant directions for improvement of national innovation system state support measures defined. The study has been carried out on the data for 2010–2020. Based on the identified parameters, recommendations have been developed to improve national innovation system effectiveness of the Russian Federation.